2008
DOI: 10.1111/j.1574-695x.2008.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of theStreptococcus gordonii glmMgene encoding phosphoglucosamine mutase and its role in bacterial cell morphology, biofilm formation, and sensitivity to antibiotics

Abstract: Phosphoglucosamine mutase (EC 5.4.2.10) catalyzes the interconversion of glucosamine-6-phosphate into glucosamine-1-phosphate, an essential step in the biosynthetic pathway leading to the formation of peptidoglycan precursor uridine 5'-diphospho-N-acetylglucosamine. The gene (glmM) of Escherichia coli encoding the enzyme has been identified previously. We have now identified a glmM homolog in Streptococcus gordonii, an early colonizer on the human tooth and an important cause of infective endocarditis, and hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 74 publications
2
30
0
Order By: Relevance
“…In the case of PNGM, recent reports indicate a growing recognition of the importance of this enzyme in bacterial virulence and infectivity (10,13,30,35,37). Therefore, inhibitors selective for the bacterial PNGMs that do not cross-react with related eukaryotic proteins, such as PGM, may find clinical utility as antimicrobial agents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of PNGM, recent reports indicate a growing recognition of the importance of this enzyme in bacterial virulence and infectivity (10,13,30,35,37). Therefore, inhibitors selective for the bacterial PNGMs that do not cross-react with related eukaryotic proteins, such as PGM, may find clinical utility as antimicrobial agents.…”
Section: Resultsmentioning
confidence: 99%
“…In Gram-negative organisms, these enzymes appear to be essential for viability (5,17,23,31). In Gram-positive organisms, reports to date suggest that this enzyme is not required for viability, but gene deletion studies show reduced virulence, increased susceptibility to antibiotics, and decreased biofilm formation (10,13,30,35,37). The role of PNGM in the virulence of Bacillus anthracis infections has not been examined, but the peptidoglycan of this organism is known to stimulate the host inflammatory response (12).…”
mentioning
confidence: 99%
“…GlmM can catalyze the conversion of glucosamine-6-phosphate to glucosamine-1-phosphate, which is an essential step in the formation of the cell wall precursor UDP-Nacetylglucosamine (25). In Streptococcus gordonii, mutations in GlmM appear to influence bacterial cell growth and morphology, biofilm formation, and sensitivity to penicillins (26). The function of GlmM in A. baumannii is currently not well-known.…”
Section: A Total Of 35 Representativementioning
confidence: 99%
“…Although GlmM is not essential for the growth of S. gordonii, its mutation may result in impaired and/or unusual peptidoglycan synthesis, leading to increased sensitivity of the glmM mutant to cell wall inhibitors and to morphological changes. All of these phenotypic changes are restored by the complementation with plasmid-borne glmM [14]. We have also shown that the glmM mutation results in increased sensitivity to polymorphonuclear leukocyte (PMN)-dependent killing, even though no differences in attachment to human PMNs were observed between the glmM mutant and the wild type of S. gordonii.…”
Section: Introductionmentioning
confidence: 88%
“…We previously reported that the S. gordonii DL1 phosphoglucosamine mutase (GlmM; EC 5.4.2.10) is involved in bacterial cell growth, morphology, biofilm formation, and sensitivity to penicillins [14]. GlmM catalyzes the interconversion of glucosamine-6-phosphate to glucosamine-1-phosphate, an essential step in the biosynthetic pathway that leads to the formation of peptidoglycan precursor uridine 5 0 -diphospho-N-acetylglucosamine [15].…”
Section: Introductionmentioning
confidence: 99%